Surfing Corona waves – instead of breaking them: Rethinking the role of natural immunity in COVID-19 policy [version 2; peer review: 2 approved, 1 approved with reservations] - Garrett W. Brown; Wim Van Damme; Elisabeth Paul; Martin Zizi; Joachim Sturmberg; Andreas Kalk; Valéry Ridde (F1000Research, 2022)
Current COVID-19 response policies have aimed to break Corona waves through non-pharmaceutical interventions and mass vaccination. However, for long-term strategies to be effective and efficient, and to avoid massive disruption and social harms, it is crucial to introduce the role of natural immunity in our thinking about COVID-19 control and prevention. We argue that any Corona control policy must appropriately balance five key elements simultaneously: balancing the various fundamental interests of the nation, as well as the various interventions within the health sector; tailoring the prevention measures and treatments to individual needs; limiting social interaction restrictions; and balancing the role of vaccinations against the role of naturally induced immunity. Given the high infectivity of SARS-CoV-2 and its differential impact on population segments, we examine this last element in more detail and argue that an important aspect of ‘living with the virus’ will be to better understand the role of naturally induced immunity in our overall COVID-19 policy response. In our eyes, a policy approach that factors natural immunity should be considered for persons without major comorbidities and those having ‘encountered’ the antigen in the past.